Se rapprocher du « réel » ou diversifier les compétences ? Un atelier coopératif de conception architecturale à l’ENSA de Clermont-Ferrand - Rémi Laporte (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Throughout the last decade, there has been a significant increase in student demand for curricula to better represent the ‘reality’ of current societal practices and issues within the French écoles nationales supérieures d'architecture (ENSA). This phenomenon echoes concern already expressed at the end of the 1960s and in the experiments that ensued. Today, it is accompanied in most ENSAs by the uncoordinated growth of architectural design courses claiming this objective and adopting cooperative and multidisciplinary teaching methods. Given that this trend encompasses a number of common features, along with a diversity of situations, and that it has received little consideration in academic literature, this article proposes to shed some light on the subject through a reflective analysis of one of these teachings. The intention is to clarify the theoretical foundations to which it refers and the didactic devices it implements to develop cooperative learning in architectural design aimed at acquiring a wider range of skills. It also seeks to characterize the nature of this cooperation and the relationships between actors that it creates, bringing them closer to the concept of social transaction. Finally, it identifies limitations and biases, both in the teaching process and in its results.